2010
DOI: 10.1016/j.jcmg.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Visceral Adipose Tissue Area and Coronary Plaque Morphology Assessed by CT Angiography

Abstract: Increased VAT area was significantly associated with NCP burden and vulnerable characteristics identified by CTA. Our findings may explain the excessive cardiovascular risk in patients with visceral adiposity, and support the potential role of CTA to improve risk stratification in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 29 publications
(32 reference statements)
8
54
0
1
Order By: Relevance
“…The amount of plaque non-calcified plaque, as well as with CT-derived features of plaque vulnerability (low attenuation, positive remodeling). 26 The present study, using high-resolution intravascular imaging, extends these previous findings, demonstrating a significant association of obesity with a thin fibrous cap and with macrophage infiltration, in addition to increased plaque burden and the amount of lipid-rich plaque. In the development and progression of atherosclerosis, macrophage infiltration of the coronary arterial wall with formation of foam cells represents a pivotal process, and macrophage-induced degradation of the fibrous cap matrix is an important contributor to plaque instability and disruption.…”
Section: Obesity Overall Plaque Burden and Plaque Phenotypesupporting
confidence: 86%
“…The amount of plaque non-calcified plaque, as well as with CT-derived features of plaque vulnerability (low attenuation, positive remodeling). 26 The present study, using high-resolution intravascular imaging, extends these previous findings, demonstrating a significant association of obesity with a thin fibrous cap and with macrophage infiltration, in addition to increased plaque burden and the amount of lipid-rich plaque. In the development and progression of atherosclerosis, macrophage infiltration of the coronary arterial wall with formation of foam cells represents a pivotal process, and macrophage-induced degradation of the fibrous cap matrix is an important contributor to plaque instability and disruption.…”
Section: Obesity Overall Plaque Burden and Plaque Phenotypesupporting
confidence: 86%
“…As similar results, apart from those studies using state-ofthe-art methodology (bidimensional echocardiography and coronary angiography) [5][6][7] , more recent investigations have shown, by cardiac computed tomography scan, a significant association between epicardial fat and coronary artery disease 14,16 . However, contrary to our study, a significant association between epicardial fat and the extent and clinical presentation of CAD has also been identified [5][6][7] .…”
Section: Discussionsupporting
confidence: 63%
“…31) Furthermore, it has been reported that visceral adipose accumulation is associated with the presence of non-calcified plaque and plaque vulnerability, as detected by CCTA. 32) It has been reported that a correlation good for CT value OK of plaque and non-calcified plaque was seen in CCTA, 33) and it has also been reported that low attenuation coronary plaques on MDCT can Data are presented as mean ± SD or number (%). V/S indicates the ratio of visceral fat to subcutaneous fat.…”
Section: Discussionmentioning
confidence: 98%